Pengenalan Pengajaran Individu dengan Tumpuan Khas kepada Modul Pengajaran dan Modul Pembelajaran - Alwiah Alsagoff, Sharifah (Penerbit Universiti Sains Malaysia, 1981)
This paper attempts to give a broad coverage of the more important types of individualised instruction. A classification of individualised instruction is given with the added purpose of introducing modules into the scope of individualised instruction. A simple classification of modules following the framework of the classification of individualised instruction is put further. Since modules have their own potentials for students and teachers, a simple guide for module writing is included.